Socialization of Healthy Curly Meatball Processing for Diabetes Mellitus in the Benteng Hilir Complex Housing: Sosialisasi Pengolahan Bakso Keriting Sehat Untuk Diabetes Melitus di Perumahan Komplek Benteng Hilir - Zuidah, Zuidah; Sumiatik, Sumiatik; Wati, Indah; Yunita, Sukma; Fadillah, Fitriani (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Diabetes Mellitus is the second type of metabolic disease characterized by increased blood sugar levels due to abnormalities in insulin production. The quite high mortality caused by diabetes mellitus is most often experienced by adults and does not cover children and teenagers. This is due to increased body weight or obesity due to an unbalanced diet. Apart from that, less activity and less exercise causes an increase in blood sugar levels. In general, this disease is often ignored and is not a disease that sufferers experience. In fact, without realizing it, his health condition began to be disturbed for quite a long time, coupled with the condition of blood glucose levels above the normal average which is a characteristic of diabetes mellitus.  Hyperglycemia can be caused by a lack of knowledge regarding how to manage diabetes mellitus. Apart from that, information about diabetes mellitus education can also be a cause of hyperglycemia. The aim of this service is to increase the knowledge of diabetes mellitus sufferers about the disease process, prevention, complications and management of diabetes mellitus. Socialization activities regarding the processing of curly meatballs for diabetes mellitus patients were carried out at the Benteng Hilir Housing Complex with a total of 22 respondents. The counseling method is carried out by conducting health checks on family members who have sufferers in the family and conducting socialization on the processing of making curly meatball food for diabetes sufferers.